Pengembangkan Motorik Halus AUD Melalui Kegiatan Meronce - Febrianti, Deriana; Arkam, Rohmad (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2024)
Early childhood education is one of the important things before children enter the primary education. At this stage, the children’s development aspects must be optimized, especially the aspect of fine motor skills development. One form of developing fine motor skills is by dancing. This article describes the strategies used by the Integrated Islamic Kindergarten of Nurussyifa, Krebet, Jambon, Ponorogo in developing fine motor skills through meronce media. The method used in this research is descriptive qualitative. Observation, interviews and documentation are the techniques used in data collection. The results of the research show that the strategy used by Integrated Islamic Kindergarten of Nurussyifa, Krebet, Jambon, Ponorogo to develop fine motor skills through meronce is effectively proved. This can be seen from field observation results that some students achieved indicator of fine motor development, such as; the child’s skills in holding objects; the child’s skills in threading objects into threads; the child’s skills in arranging and grouping objects; and the child’s skills in training eye and hand coordination focus.